As-Sabak Al-Mu‘Jami fi Diwan As-Suba‘Iyat li ‘Isa Albi Abu Bakr: Dirasah Tahliliyah Naqdiyah - Khalil Mohammad Usman Gbodofu (el Harakah: Jurnal Budaya Islam, 2019)
يتبوأ الشعر في التراث العربي النيجيري مكانة عالية جدا، يقرض علماء هذه البلاد أشعارهم في أغراض مختلفة، إذ يوجد في أشعارهم الرثاء والمدح والوصف ونحو ذلك، وهؤلاء العلماء يستخدمون أساليب متنوعة، فمنهم من يسلك مسلك البحور الخليلية المعروفة، ومنهم من يؤثر البحور المهملة، ومنهم من ينتهج منهج أصحاب الرباعيات أو الخماسيات أو السداسيات أو السباعيات أو غيرها. وأما هذه الورقة فإنها تهدف إلى إلقاء الضوء على أنماط السبك المعجمي الواردة في ديوان «السباعيات» للدكتور عيسى ألبى أبو بكر. تمثّل هذه الظاهرة فنّا جديدًا للدراسة النصية، وصورة شفافة للشكل المعجمي الذي يتناوله الدارسون المعاصرون في الكتب المقدسة، وفي بعض أعمال العلماء القدماء والمحدثين. استطاع الباحث في هذه الورقة أن يقف عند حياة الشاعر وأعماله العلمية والفنّيّة، وعند مضامين ديوان السباعيات، وتمكّن على دراسة أهم عناصر السبك المعجمي، حيث طبّق هذه العناصر على أبيات الديوان مركّزا على التكرار، والترادف، والمصاحبة اللغوية؛ مع التقويم النقدي والإشارة -في بعض الأحايين- إلى السبب الذي أدى بالشاعر إلى قرض قصائده.Poetry in the Nigerian Arabic Heritage has attained a high level, as Arabic scholars used to compose their poems in different themes including elegy, panegyrics, description and others, while different styles have been explored. In the process of writing the poems, some of them applied the well-known Khalilian prosodic metres, others applied uncommon ones, while the rest was known to write poems in tetragon, pentagon, hexagon and heptagon. The main focus of this paper was to illuminate on the adopted styles of lexicographical shaping in “Diwan As-Subaiyyat” by Isa Alabi Abubakar. This phase stands out as a new art of textual study and a reflect of contemporary lexicographical form which researchers used to study aspect of scriptures and the works of the ancient and modern scholars. The researcher was able to give an account of the poet’s biography and his literary and artistic works particularly contents of the Diwan As-Subaiyyat. The researcher, in the course of studying the components of the lexicographical shaping in the Diwan, elucidates the values of repetition, synonymy, linguistic homogeneity with critical comments pointing into the reason that led the poet to writing the poems. In conclusion, the researcher summarized this study, presented its findings, before mentioning the bibliographies and references.